The 'Bermuda Triangle' of orthostatic hypotension, cognitive impairment and reduced mobility: prospective associations with falls and fractures in The Irish Longitudinal Study on Ageing. - O'Neill, Desmond; Kennelly, Sean; Romero-Ortuno, Roman; Briggs, Robert; Kenny, Rose; Cunningham, Conal (My University, 2023)
Background: Orthostatic hypotension (OH), cognitive impairment (Cog) and mobility impairment (MI) frequently co- occur in older adults who fall. This study examines clustering of these three geriatric syndromes and ascertains their relationship with future falls/fractures in a large cohort of community-dwelling people ≥ 65 years during 8-year follow-up. Methods: OH was defined as an orthostatic drop ≥ 20 mmHg in systolic blood pressure (from seated to standing) and/or reporting orthostatic unsteadiness. CI was defined as Mini Mental State Examination ≤ 24 and/or self-reporting memory as fair/poor. MI was defined as Timed Up and Go ≥12 s. Logistic regression models, including three-way interactions, assessed the longitudinal association with future falls (explained and unexplained) and fractures. Results: Almost 10% (88/2,108) of participants had all three Bermuda syndromes. One-fifth of participants had an unexplained fall during follow-up, whereas 1/10 had a fracture. There was a graded relationship with incident unexplained falls and fracture as the number of Bermuda syndromes accumulated. In fully adjusted models, the cluster of OH, CI and MI was most strongly associated with unexplained falls (odds ratios (OR) 4.33 (2.59–7.24); P < 0.001) and incident fracture (OR 2.51 (1.26–4.98); P = 0.045). Other clusters significantly associated with unexplained falls included OH; CI and MI; MI and OH; CI and OH. No other clusters were associated with fracture. Discussion: The ‘Bermuda Triangle’ of OH, CI and MI was independently associated with future unexplained falls and fractures amongst community-dwelling older people. This simple risk identification scheme may represent an ideal target for multifaceted falls prevention strategies in community-dwelling older adults.
PUBLISHED
Keywords: orthostatic hypotension, falls, cognitive impairment, mobility, fracture, older people; Ageing